Highly efficient catalysts for oxygen reduction using well-dispersed iron carbide nanoparticles embedded in multichannel hollow nanofibers. Issue 35 (24th August 2020) - Xia, Hongyin; Zhang, Shan; Zhu, Xiaoqing; Xing, Huanhuan; Xue, Yuan; Huang, Bolong; Sun, Mingzi; Li, Jing; Wang, Erkang
Abstract : Well-dispersed and highly active iron carbide nanoparticles encapsulated in multichannel hollow nanofibers (Fe3 C@MHNFs) were synthesized via simple electrospinning and calcination steps, exhibiting highly efficient activity and robust durability for oxygen reduction. Abstract : Engineering catalytic materials into appropriate structures to get the structural benefits is vital for harvesting unprecedented catalytic efficiency in the oxygen reduction reaction (ORR). Herein, well-dispersed and highly active iron carbide nanoparticles (Fe3 C NPs) were encapsulated in multichannel hollow nanofibers (MHNFs) to construct Fe3 C@MHNF catalysts, which were synthesized via simple electrospinning and calcination steps. The well-defined inner channels with high conductivity and a porous structure enable the rapid electron transfer and mass transport for the ORR. And the resulting hybrid electrocatalyst with Fe3 C NPs serving as active sites exhibits highly efficient activity with a half-wave potential of 0.90 V vs. the reversible hydrogen electrode (RHE), which surpasses that of the commercial platinum on carbon (Pt/C) catalyst (a half-wave potential of 0.84 V vs. RHE). The catalyst shows robust durability with negligible activity decay after 10 000 cycles. Density functional theory calculations confirm that the introduction of MHNFs significantly improves the electron transfer and exchange capability. The formed interfacial region not only induces linear correlation in both electronic structures and binding energies but also alleviates the barrier of site-to-site electron transfer between Fe3 C NPs and MHNFs for the ORR process.